Integrated System Design: Promoting the Capacity of Sociotechnical Systems for Adaptation through Extensions of Cognitive Work Analysis - Naikar, Neelam; Elix, Ben (Frontiers in Psychology, 2016)
This paper proposes an approach for integrated system design, which has the intent of facilitating high levels of effectiveness in sociotechnical systems by promoting their capacity for adaptation. Building on earlier ideas and empirical observations, this approach recognizes that to create adaptive systems it is necessary to integrate the design of all of the system elements, including the interfaces, teams, training, and automation, such that workers are supported in adapting their behavior as well as their structure, or organization, in a coherent manner. Current approaches for work analysis and design are limited in regard to this fundamental objective, especially in cases when workers are confronted with unforeseen events. A suitable starting point is offered by cognitive work analysis, but while this framework can support actors in adapting their behavior, it does not necessarily accommodate adaptations in their structure. Moreover, associated design approaches generally focus on individual system elements, and those that consider multiple elements appear limited in their ability to facilitate integration, especially in the manner intended here. The proposed approach puts forward the set of possibilities for work organization in a system as the central mechanism for binding the design of its various elements, so that actors can adapt their structure as well as their behavior—in a unified fashion—to handle both familiar and novel conditions. Accordingly, this paper demonstrates how the set of possibilities for work organization in a system may be demarcated independently of the situation, through extensions of cognitive work analysis, and how it may be utilized in design. This lynchpin, conceptualized in the form of a diagram of work organization possibilities, is necessary for creating adaptive systems. Future research should focus on validating these concepts and establishing the feasibility of implementing them in industrial contexts.